Specific heat of the periodic Anderson model: From weak to strong coupling - Peres, Nuno (2020)
We study the temperature dependence of the specific heat in the periodic Anderson model as function of the on-site Coulomb interaction, hybridization, and position of the f electrons energy level. At strong coupling (U = infinity) we use slave bosons, whereas at weak coupling we use a simple Hartree-Fock decomposition. We find that both in the strong and weak coupling limits the specific heat of the system presents a multiple peak structure in a mean field treatment. We believe these features to be related to band-shape effects. The temperature evolution of the low-temperature peak position on the model parameters for the non-half-filled nonsymmetric case is discussed.